Poetic of the gap in the poem “Joggers” By the poet Nizar QUABANI - benwadeh, sihem; baghora, yacine (The Notebooks of the Algerian Poetics Laboratory Journal, 2025)
literary texts as a departure from the ordinary. The Arab poet resorts to it because of its aesthetic dimension and intellectual role in literary work. Nizar Qabbani is one of the most prominent contemporary poets who used this technique in their poetic creations. One of his most famous poems in this section is the poem The problem is "The Joggers", as it is a poem that translates a stance against normalization and against the miserable peace, and accordingly this study comes to investigate the mechanisms of employing stylistic displacement and its aesthetic dimensions on the structural and semantic level, to answer the following problem: What is the extent of the success of the displacement style in performing the poet's political message in the poem of the joggers ? What are the mechanisms that Nizar relied on in the style of displacement? Based on the nature of the study, it adopts some of the stylistic approaches as a guiding and framed research pillar to answer the research problem and what is related to it.